Mild cognitive impairment impacts health outcomes of patients with atrial fibrillation undergoing a disease management intervention - Ball, Jocasta (Open Heart, 2018)
OBJECTIVE: Mild cognitive impairment (MCI) is prevalent in atrial fibrillation (AF) and has the potential to contribute to poor outcomes. We investigated the influence of MCI on survival and rehospitalisation in patients with chronic forms of AF undergoing a home-based, AF-specific disease management intervention (home-based intervention (HBI)) or standard management (SM). METHODS: The Montreal Cognitive Assessment tool was administered at baseline (a score of <26/30 indicated MCI) in patients with AF randomised to HBI versus SM. Post hoc analyses of mortality and rehospitalisations during a minimum 24-month follow-up were conducted in the overall cohort and in each study group separately. RESULTS: Of 260 patients (mean age 72±11, 47% female), 65% demonstrated MCI on screening (34% in SM; 31% in HBI). Overall, the number of days spent alive and out-of-hospital during follow-up (P=0.012) and all-cause rehospitalisation were influenced by MCI during follow-up (OR 3.16 (95% CI 1.46 to 6.84)) but MCI did not influence any outcomes in the SM group. However, survival was negatively influenced by MCI in the HBI group (P=0.036); those with MCI in this group were 5.6 times more likely to die during follow-up (OR 5.57 (95% CI 1.10 to 28.1)). Those with MCI in the HBI group also spent less days alive and out-of-hospital than those with no MCI (P=0.022). MCI was also identified as a significant independent correlate of shortest duration of event-free survival (OR 3.48 (95% CI 1.06 to 11.4)), all-cause rehospitalisation (OR 3.30 (95% CI 1.25 to 8.69)) and cardiovascular disease (CVD)-related rehospitalisation (OR 2.35 (95% CI 1.12 to 4.91)) in this group. CONCLUSIONS: The effectiveness of home-based, disease management for patients with chronic forms of AF is negatively affected by comorbid MCI. The benefit of adjunctive support for patients with MCI on CVD-related health outcomes requires further investigation.